1974
DOI: 10.1111/j.1471-4159.1974.tb12211.x
|View full text |Cite
|
Sign up to set email alerts
|

D‐galactose Transport by Synaptosomes Isolated From Rat Brain

Abstract: Abstract— Synaptosomes prepared by differential and Ficoll density gradient centrifugation took up d‐galactose by two saturable transport systems: one. a high affinity system with a Km of 0‐25 mn and Vmax of 075 nmol/mg protein 3 min, the other, a low affinity system with a Km of 47 mM and a Vmaxof 135 nmol/mg protein/3 min. The high affinity system was inhibited by 1‐5 mM phlorizin but was unaffected by the absence of sodium ion or the presence of 1 mM ouabain. The low affinity system was unaffected by phlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Litters were reduced to seven on the day of delivery, and young rats were weaned onto their respective maternal diets at 19 days of age. Synaptosomes were isolated as described (8). For young rats, modified Ficoll gradients were used.…”
Section: Methodsmentioning
confidence: 99%
“…Litters were reduced to seven on the day of delivery, and young rats were weaned onto their respective maternal diets at 19 days of age. Synaptosomes were isolated as described (8). For young rats, modified Ficoll gradients were used.…”
Section: Methodsmentioning
confidence: 99%
“…When the gray and white matters were compared, higher radioactivity was found in the gray matter, which was also higher in mice after [U-14C]glucose injection (44). Warfield et al (54) reported that the brain of rat and chick had the Leloir pathway, but the activities of transferase (34) and UDP-galactose-4-epimerase (7) which catalyze the conversion of UDP-galactose to UDP-glucose, were low in the brain.…”
Section: R-mentioning
confidence: 99%
“…After this period, activities of these enzymes decrease and the epimerase attains adult level at 20 days after birth, but the galactokinase and transferase at 35 days (2). In the adult animals, galactose may also be utilized as an energy source in certain organs such as the kidney (27,33,39,51), small intestine (36), brain (34,47,54) and myocardium (34).…”
Section: Distributionmentioning
confidence: 99%
“…Galactose can be taken up into the brain across the blood-brain barrier by the same carrier mechanism of glucose (7,9,24). The presence of the enzymes of the Leloir pathway in rat and chick brain has been well documented (3,5,8,19,40). On the other hand, low galactose-1-P uridyltransferase activity in the rat brain has been reported by Musick et al (21).…”
Section: Discussionmentioning
confidence: 90%
“…It is generally accepted that galactose is conveyed to the liver, where it is converted to glucose by the Leloir pathway (18). In the previous studies, enzyme activities belonging to this pathway have been found in the liver (3, 5, 8, 33), kidney (3, 5, 8, 16, 20, 25, 34), intestine (23), brain (21,32,40) and myocardium (21) etc. On the other hand, it has been reported that galactose is an important constituent of the glycoproteins, glycolipids and mucopolysaccharides (1,4,10,13,14,15,22).…”
mentioning
confidence: 99%